Unlocking the healing power of psilocybin: an overview of the role of psilocybin therapy in major depressive disorder, obsessive-compulsive disorder and substance use disorder - Szafoni, Sandra; Gręblowski, Piotr; Grabowska, Klaudia; Więckiewicz, Gniewko (Frontiers in Psychiatry, 2024)
Resistance to traditional treatment methods is still a major obstacle in modern psychiatry. As a result, several studies are currently being conducted to find effective alternatives to traditional therapies. One of these alternatives is psilocybin, a psychedelic substance that has been tested in clinical trials as an adjunct to psychotherapy. These studies focus on patients with major depressive disorder (MDD), obsessive-compulsive disorder (OCD) and substance use disorder (SUD), particularly alcohol and nicotine dependence. This article looks at the current understanding of psilocybin, including data from clinical trials conducted, psilocybin's mechanism of action, its safety and the level of risk associated with it.